Exosome derived from stem cell: A promising therapeutics for wound healing - Lv, Hui; Liu, Hanxiao; Sun, Ting; Wang, Han; Zhang, Xiao; Xu, Wei (Frontiers in Pharmacology, 2022)
Wound occurs when the epidermis and dermis of skin are damaged internally and externally. Traditional wound healing method is unsatisfactory, which will prolong the treatment time and increase the treatment cost that bring economic and psychological burden to patients. Therefore, there is an urgent need for a new method to accelerate wound healing. As a cell - free therapy, exosome-derived from stem cell (EdSC) offers new possibilities for wound healing. EdSC is the smallest extracellular vesicle secreted by stem cell with diameters of 30-150 nm and lipid bilayer structure. Previous studies have found that EdSC can participate in and promote almost all stages of wound healing, including regulating inflammatory cells, improving activation of fibroblasts, keratinocytes and endothelial cells, and adjusting the ratio of collagen Ⅰ and Ⅲ. We reviewed the relevant knowledge of wound, summarized the biogenesis, isolation and identification of exosomes, and clarified the pharmacological role of exosomes in promoting wound healing. This review provides knowledge support for the pharmacological study of exosomes.